“Transforming Faith: The Impact of Digital Media and Technology on Community Engagement in Contemporary Pentecostalism" in Southern Africa - Lindah Tsara; Tsitsi Mwapfaa (Pharos Journal of Theology, 2025)
This research explores the significant influence of digital media and technology on community involvement in modern Pentecostalism in Southern Africa, with particular emphasis on the United Family International Church (UFIC) and the Prophetic, Healing, and Deliverance Ministries (PHD). As society embraces a digital age, these religious organizations have adeptly integrated various forms of media, including radio, television, social media, and mobile applications, to enhance their reach and foster connections with followers globally. This research aims to highlight how such integration serves as an evangelistic tool that transcends geographical and cultural barriers and addresses the diverse needs of congregants, particularly younger demographics. The study uses qualitative research methods to emphasize religious groups' need to harness media and technology for spiritual development and practical theological discourse, empowering believers to engage meaningfully within their local contexts and on broader platforms. The findings illustrate how the strategic use of technology has transformed traditional worship practices and facilitated community involvement, especially during physical constraints, such as during the COVID-19 pandemic. Conclusively, this research underscores the adaptability and innovation of Pentecostalism in utilizing available resources to spread the gospel and strengthen community cohesion. This study implies that the integration of technology has transformed traditional worship practices in an important and meaningful manner.